STAFF PERFORMANCE MANAGEMENT AT CAR SERVICE BASED ON ANALYTICAL INDICATORS - Vladimir A. Trubitsyn (Вестник Северо-Кавказского федерального университета)
There is a view on a newly developed method for determining analytical indicators regarding the staff at a car service. The author used an approach for integrating and combining parameters of a lower level into an overall comprehensive assessment.